The dark mirror of capital: on post-neoliberal formations and the future of education. Issue 2 (4th March 2019) - Means, Alexander J.; Slater, Graham B.
ABSTRACT: This paper examines how transformations in political economy and digital technology point toward potential post-neoliberal futures. Outlining the contours of a crisis of neoliberal hegemony, the authors explore how technological developments have contributed to political economic dynamics of market failure and oligarchic capture, resulting in new forms of digital precarity. As evidence, the paper examines a specific post-neoliberal discourse called neoreactionism (NRx), which has developed out of the distinct culture of Silicon Valley. NRx represents a specific vision for resolving conflicts inherent to neoliberalism by intensifying oligarchic capture and the acceleration of technology. While NRx is a techno-authoritarian discourse that exists largely outside of mainstream academic discussions, it is indicative of how transformations in late capitalism are fueling the rise of anti-democratic consciousness and identification. In response, the authors conclude with suggestions for developing post-neoliberal approaches to educational studies that are able to challenge these troubling reactionary trends.